L’esperienza delirante - Raballo, Andrea; Serra, Raffaella (Il sogno della farfalla, 2020)
In psychopathology the definition and recognition of delusions is of central importance. This issue is fundamental not only for diagnostic and therapeutic reasons but also from an epidemiological point of view. However, starting from Jasper’s theory, the definition of delusion has remained elusive and unsatisfactory due to the persistence of many conceptual ambiguities. Delusions have been sometimes superficially considered as abnormal unquestionable beliefs against the backdrop of more acceptable ideas or as the result of a solipsistic and idiosyncratic immersion into the world. It becomes possible to understand the basis of delusions if these are seen not as a belief or erroneous judgment on reality but rather as a manifestation within a psychopathological and psychic-existential context. The roots of this phenomenon are lost in childhood and adolescence stories and are not simply accessible through the anamnesis and psychiatric interview. In this sense the origin of delusion can be more clearly identified as the result of the annulment pulsion.